Alasan Singapura Memperpanjang Kontrak Pergelaran Formula 1 Grand Prix Tahun 2022 - Ine Dwi Rochmawati (University of Jember, 2023)
Singapore has renewed its Formula 1 Grand Prix contract in 2022 even though it has not benefited from the racing event for two years due to pandemic of Covid-19. This study aims to find out Singapore's reasons for extending the contract of the Formula 1 Grand Prix in 2022. This research uses qualitative methods. The theory of liberalism is used in this study to find out and understand Singapore's reasons for extending the 2022 Formula 1 Grand Prix contract. The result of this study is the Formula 1 Grand Prix Extention by Singapore is a form of the country’s nation branding efforts. Nation branding carried out by Singapore through the Formula 1 Grand Prix is divided into six aspects, namely tourism, cultural heritage, government, community, exports and investment. The success of nation branding in this event is the increase of country's image which is marked by the increase in foreign tourist visits to Singapore.